Assessment of knowledge, attitudes and practices (KAP) on HIV/AIDS among peer educators and students at the Tshwane University of Technology - Basini, Dixie Thomas (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.